(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Every year, millions of people lose their lives to cancer, making it one of the most common and deadly diseases of our time. In addition to genes, food habits, smoking, nutritional behaviours, radiation, and other environmental factors, there are numerous other factors that contribute to disease. Phytocompounds derived from medicinal herbs and their derivatives are increasingly being recognised as useful complementary cancer treatments. Herbal drugss used in conjunction with conventional therapeutics have been shown in numerous clinical studies to improve cancer patients’ survival, immune function, and quality of life (QOL). Only chemotherapy and radiation treatments have proven effective against cancer so far however, these treatments are often toxic and lethal. Ayurveda knowledge combined with herbal drugs concepts could provide better drug leads for the inhibitory treatment of cancer. Alternative and less toxic medication is desperately needed. Anticancer and antioxidant-rich medicinal plants abound in nature, and many of these can be used to completely eradicate cancer. The search for natural cancer drugs began in the late 1960s and resulted in the discovery of vincristine, vinblastine, campthothecin, and taxol (among other things). This review focuses on herbal drugs derived from natural sources for the discovery of new drug leads for the treatment of cancer.